2019
DOI: 10.1176/appi.ps.201700561
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Correlates of Assertive Community Treatment (ACT) and ACT-Like Programs: Results From the 2015 N-MHSS

Abstract: The study examined the availability and characteristics of assertive community treatment (ACT) programs across mental health treatment facilities in the United States.Methods: Prevalence and correlates of facilities that reported offering ACT, broadly defined as intensive community services for serious mental illness provided by multidisciplinary teams in the clients' natural settings and including both ACT and "ACT-like" programs, were examined by using data from the National Mental Health Services Survey. Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Deinstitutionalization of the 1950s-1970 s was followed by several other major social changes that stimulated the development of novel community-based public mental health services. While the effectiveness, and cost-effectiveness of these specialized services has been demonstrated in randomized trials [62,36,63,25], evaluation of the acessabiity and effectiveness of such programs in the context of large regional and national service systems is a far more challenging task, and remains to be undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Deinstitutionalization of the 1950s-1970 s was followed by several other major social changes that stimulated the development of novel community-based public mental health services. While the effectiveness, and cost-effectiveness of these specialized services has been demonstrated in randomized trials [62,36,63,25], evaluation of the acessabiity and effectiveness of such programs in the context of large regional and national service systems is a far more challenging task, and remains to be undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Local studies based on Medicaid data do show that community programs continued to provide ACT and ACT-like services to the most seriously mentally ill and functionally impaired adults [64], though one recent survey suggested that less than 20% of non-VA community mental health facilities offer ACT [65] and even fewer offer other community services such as peer support, employment, and housing services [66]. While most research has focused on either people who use less intensive services (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Local studies based on Medicaid data show that community programs continued to provide ACT and ACT-like services to the most seriously mentally ill and functionally impaired adults [56], though a recent survey suggested that less than 20% of non-VA community mental health facilities offer ACT [57] and even fewer offer other community services such as peer support, employment, and housing services [58]. While most research has focused on either people who use less intensive services (i.e.…”
Section: Discussionmentioning
confidence: 99%